La desintegración informática - escuela (1998)
The article makes a deep analysis about the role computer science plays in the educational institution, its boundaries and possibilities, and the necessity of readjusting technological advances in order to place them in an instrumental context, submitted to the school's forming function.The limit and the sense of new technologies and the desired relationship between human formation and information are also stated in this paper.